Discover the User Satisfaction of Overseas Wechat Official Accounts through Kano Model - Liang , Ying; Wudhikarn, Ratapol (International Journal of Membrane Science and Technology, 2023)
In the digital age, rapid socio-economic shifts have intensified competition among enterprises, particularly in the realm of new media. New media companies leverage fan economy dynamics to gain prominence. As competition diversifies across dimensions like price, quality, service, and user experience, the common goal remains user satisfaction. This requires understanding latent user needs, integrating a user-centric approach in product development, and aligning offerings with genuine user requirements